Mental Health Status of the Elderly Chinese Population During COVID-19: An Online Cross-Sectional Study - Zhou, Rui; Chen, Hao; Zhu, Lin; Chen, Ying; Chen, Boyan; Li, Ying; Chen, Zhi; Zhu, Haihong; Wang, Hongmei (Frontiers in Psychiatry, 2021)
Abstract Background: COVID-19 not only threatened the public’s physical health but also brought unbearable psychological pressure, especially for those vulnerable groups like the elderly. However, studies on the psychological status of older adults during this public health emergency remained scant. This study aims to investigate the mental health status among the elderly Chinese population during COVID-19 pandemic and determine the influencing factors of psychological symptoms. Methods: From February 19 to March 19, 2020, an online survey was administered to Chinese older adults using a convenience sampling method. Information on demographic data, health status and other epidemic related factors were collected. Specifically, the study defined the psychological status as five primary disorder–depression, neurasthenia, fear, anxiety, and hypochondria– which were assessed by the Psychological Questionnaire for Emergent Event of Public Health (PQEEPH). Standard descriptive statistics and multiple logistic regression analyses were conducted to analyze the data. Results: Of 1501 participants recruited from 31 provinces in China, 1278 were valid for further analysis. Participants’ scores on each sub-scale were described in median and interquartile (M(Q)) (depression, 0.00(0.33)); neurasthenia, 0.00(0.40) ; fear, 1.00(0.83); anxiety, 0.00(0.17) ; hypochondria, 0.00(0.50) ). Chronic diseases (depression p=0.001; neurasthenia p<0.001; fear p= 0.023; anxiety p<0.001; hypochondria p=0.001) and the BMI index (depression p=0.015; neurasthenia p= 0.046; fear p= 0.016; anxiety p=0.015; hypochondria p=0.013) had significant impacts on all of the five sub-scales. Specifically, the rural dwellers had a higher level of neurasthenia, fear, and hypochondria. Besides, education level (p=0.035) and outbreak risk level (p=0.004) had significant impacts on the depression. Higher household monthly income per capita (p=0.031), and the community-level entry/exit control(p=0.011) are factors against anxiety. Conclusions: Most elderly residents reported mild negative emotions during COVID-19 and more attention should be paid to the recognition and alleviation of fear. Our findings also identified factors associated with the mental health status of the elderly, which is of practical significance in the design and implementation of psychological interventions for this vulnerable population during COVID-19 and future emerging diseases.